2017
DOI: 10.1080/14728222.2017.1319938
|View full text |Cite
|
Sign up to set email alerts
|

Competitive endogenous RNA network: potential implication for systemic lupus erythematosus

Abstract: Competitive endogenous RNA (ceRNA) hypothesis proposes that RNA transcripts, both coding and non-coding, crosstalk with and coregulate each other using microRNA response elements (MREs). CeRNA analysis tremendously expands functional information of coding and non-coding RNAs. Mounting evidence have shown that various types of RNAs, including pseudogenes, long non-coding RNAs, circular RNAs, and messenger RNAs, can function as ceRNAs in distinct physiological and pathophysiological states. Many validated ceRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(44 citation statements)
references
References 121 publications
0
44
0
Order By: Relevance
“…Therefore, it is of great significance to further explore the relationship between the changes in new gene function and the development and malignant characteristics of glioma tumours, to reveal the precise molecular mechanism of its occurrence and development, to develop reasonable therapeutic drugs and determine the prognosis and to further improve the treatment of glioma and the prognosis of glioma patients. 22 In addition, lncRNA, as ceRNA, plays an important role in carcinogenesis. 21 A number of studies have shown that lncRNAs can participate in the regulation of various biological processes through ceRNA mechanism, such as muscle differentiation, cell resistance, neural cell differentiation, etc.…”
Section: Discussionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of great significance to further explore the relationship between the changes in new gene function and the development and malignant characteristics of glioma tumours, to reveal the precise molecular mechanism of its occurrence and development, to develop reasonable therapeutic drugs and determine the prognosis and to further improve the treatment of glioma and the prognosis of glioma patients. 22 In addition, lncRNA, as ceRNA, plays an important role in carcinogenesis. 21 A number of studies have shown that lncRNAs can participate in the regulation of various biological processes through ceRNA mechanism, such as muscle differentiation, cell resistance, neural cell differentiation, etc.…”
Section: Discussionsmentioning
confidence: 99%
“…21 A number of studies have shown that lncRNAs can participate in the regulation of various biological processes through ceRNA mechanism, such as muscle differentiation, cell resistance, neural cell differentiation, etc. 22 In addition, lncRNA, as ceRNA, plays an important role in carcinogenesis. 23 For example, in ovarian cancer, lncRNA HOST2 upregulates the expression of HMGA2 and c-MYC by the competitive binding with let-7b-5p, thereby promoting the occurrence and development of ovarian cancer.…”
Section: Discussionsmentioning
confidence: 99%
“…39 We concerned that LINC00094 was up-regulated in Abeta 1-42 -in- Emerging evidence indicated that certain lncRNAs can served as a competitive endogenous RNA ("ceRNA") to regulate downstream gene expression and biological function. 43 The results of Dual-luciferase reporter assay and RIP assay showed that miR-224-5p (miR-497-5p) was enriched by LINC00094 and sponge LINC0094 in a sequence-specific manner, respectively. 41 TGFB2-OT1 regulates autophagy in vascular endothelial cells (VECs) via sponging miR-3960, miR-4488, miR-4459.…”
Section: Discussionmentioning
confidence: 99%
“…MRE has been identified to be a highly conserved sequence and used as a new language to explore ceRNA regulation network. 43 The results of Dual-luciferase reporter assay and RIP assay showed that miR-224-5p (miR-497-5p) was enriched by LINC00094 and sponge LINC0094 in a sequence-specific manner, respectively. These results supported the hypothesis that LINC00094 regulates BBB permeability in AD microenvironment.via sponging miR-224-5p/miR-497-5p.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, up to 65 731 circRNAs are detected in human brain samples and neuronal circRNAs show significant conservation in both expression and sequence . As for the physiological function of circRNAs, they can serve as miRNA sponges and thereby sequester miRNAs from their natural mRNA targets . For example, Sry and ciRS‐7 can serve as sponges of miR‐138 and miR‐7, respectively .…”
Section: Introductionmentioning
confidence: 99%